The Echo Maker, de Richard Powers – le retour au pays - Nathalie Cochoy (Caliban: French Journal of English Studies)
In The Echo Maker, the annual return of cranes to a precise place, in Nebraska, reveals the respectful relationship that, since Moby-Dick, American writers have established with the land. Far from attempting to coerce nature into framed descriptions, Richard Powers shows how essential an acknowledgement of the elusiveness of the land is. Structured like a flight of migratory birds, the novel illustrates how literature and sciences are complementary in their approach of the human and nonhuman worlds. It reveals the commonness of places—the links between men and animals but also the links between the members of the community, in their most ordinary lives. Indeed, it is the salutary poetic dimension of the prosaic that the novel eventually unveils.